Evaluasi Tata Kelola Teknologi Informasi Universitas Multimedia Nusantara Periode 2016 - Wella Wella; Stella Aprilia Sirapanji (Universitas Multimedia Nusantara, 2016)
Not only for enterprises, educational institution use information technology for teaching and learning. Universitas Multimedia Nusantara (UMN) aware that IT is very important in the world of education. To measure effectiveness in IT governance, UMN needs audit information system using the COBIT 5.0 framework in order to determine the extent to which the performance of the IT department and also know the UMN produce a solution to every problem is unresolved. The object of this study is the Department of Information Technology UMN. This study uses COBIT 5.0 with 5 domains that is Evaluate, Direct and Monitor (EDM); Align, Plan and Organize (APO); Build, Acquire and Implement (BAI); Deliver, Service and Support (DSS) and Monitor, Evaluate and Assess (MEA). At 37 the process of the 5 IT governance domains belonging to COBIT 5.0 by using the stages of COBIT 5.0 is filtered into 10 processes. The data collection was done by interviewing the manager of IT department, observation of documentation, and the distribution of questionnaires to the two heads of divisions within the IT department manager for IT departments demand UMN. The results of this study each domain is at 1 st level (incomplete). Capability level values achieved by EDM01 is 81.84%, EDM02 is 76.17%, APO01 is 73.28%, APO02 is 67.72%, APO03 is 52.30%, APO05 is 66.44%, APO07 is 64.20%, APO08 is 75.19%, BAI01 is 56.33%, and BAI02 is 65.20%. Keyword: Audit Information System, Capability Level, Framework COBIT 5.0, IT Governance